Effect of a community-based lifestyle intervention on predictors of behavior change regarding a healthy plant-based diet—The Healthy Lifestyle Community Program (cohort 2) - Kettler, Carmen; Weber, Ragna-Marie; Anand, Corinna; Husain, Sarah; Koeder, Christian; Schoch, Nora; Michaelsen, Maren M.; Esch, Tobias; Englert, Heike (Frontiers in Public Health, 2025)
BackgroundImplementing healthy behaviors, particularly a healthy plant-based diet, can play a key role in preventing non-communicable diseases (NCDs). However, behavior change initiation and maintenance can be challenging. The objective was to test, if the Healthy Lifestyle Community Program (cohort 2; HLCP-2) was effective in changing psychological constructs regarding eating behavior.MethodsA 24-month non-randomized controlled intervention study with a community-based approach in rural Germany was conducted. The intervention group (IG) received a 10-week intensive lifestyle intervention aiming to improve NCD risk factors, followed by a 22-month alumni phase. The control group (CG) received no intervention. Participants completed questionnaires at six measurement time points to assess psychosocial constructs of behavior change derived from the Health Action Process Approach, including action/coping planning, action self-efficacy (SE), maintenance SE, recovery SE, and eating behavior. An exploratory analysis with inter- and intra-group comparisons regarding different scores of HAPA constructs was conducted. Covariate-adjusted comparisons were performed using multiple linear regression models. Additionally, bivariate correlations between these constructs and the healthy plant-based diet index (hPDI) were examined.ResultsA total of 186 participants (IG: n = 111; CG: n = 75) were analyzed. In the IG, all HAPA scores increased significantly at all measurement time points compared to baseline, with the highest impact after the intensive phase (p < 0.001). Between-group comparisons for action/coping planning and action SE were significant at all measurement time points, while results for maintenance and recovery SE were inconsistent in the study course. Adjusting for covariates did not substantially alter the results. After 10 weeks, only recovery SE correlated significantly with hPDI (ρ = 0.289, p = 0.004).ConclusionParticipation in the HLCP-2 intervention resulted in improvements in planning health-promoting behaviors, action, maintenance, and recovery SE. Further research is required to determine whether an increase in action planning and SE leads to changes in dietary behavior.Clinical trial registrationGerman Clinical Trials Register DRKS (https://drks.de/search/de; reference: DRKS00018775; retrospectively registered).